PENDEKATAN ANALISIS DISKRIMINAN PADA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Astuti, Cindy Cahyaning; Wiguna, Akbar; Ariyanti, Novia (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
Online learning is solution that implemented in the midst of the COVID-19 pandemic. Since COVID-19 pandemic, the learning process at UMSIDA used 100% online learning with UMSIDA e-learning media.It can accommodate students to carry out distance learning. So far, research has not been carried out readiness of students to take part in online learning during the COVID-19 pandemic. Based on this, this research focuses on knowing the readiness of students to take online lectures during the COVID-19 pandemic using discriminant analysis. Based on the results of the analysis of the predictor variable, the strongest differentiator is the flexibility of lecture time (X1) because the variable with the largest coefficient. This means that the variable time flexibility (X1) has the strongest dividing power against online learning readiness during the COVID-19 pandemic. In addition, it also known that according to the student's perspective, the learning media that makes interaction with lecturers the most easy and the learning media that makes it the most easy to understand the material is using video conferencing (Zoom, Google Meet, etc.). On the other hand, choice of the learning system most chosen by students when the COVID-19 pandemic ends is online system 30% and offline 70%.